2020
DOI: 10.1016/j.nicl.2019.102119
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-parietal engagement in response inhibition is inversely scaled with attention-deficit/hyperactivity disorder symptom severity

Abstract: HighlightsA novel Go/No-go task points to a critical role for the IPS in response inhibition.IPS engagement in response inhibition is scaled back with ADHD symptom severity.Fronto-parietal connectivity increases when response inhibition is challenging.Connectivity modulation is also scaled back with ADHD symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 87 publications
(112 reference statements)
1
16
0
Order By: Relevance
“…The behavioural data revealed the typical response inhibition deficits in AD(H)D, i.e. an increase in false alarms relative to healthy controls ( Kolodny et al, 2020 , Metin et al, 2012 , Pievsky and McGrath, 2018 ), and worse response inhibition performance in the ADHD group than the ADD group ( Bluschke et al, 2016b ). The analysis of source-level theta band activity showed that theta power was stronger during trials requiring response inhibition than in those requiring response execution.…”
Section: Discussionmentioning
confidence: 91%
“…The behavioural data revealed the typical response inhibition deficits in AD(H)D, i.e. an increase in false alarms relative to healthy controls ( Kolodny et al, 2020 , Metin et al, 2012 , Pievsky and McGrath, 2018 ), and worse response inhibition performance in the ADHD group than the ADD group ( Bluschke et al, 2016b ). The analysis of source-level theta band activity showed that theta power was stronger during trials requiring response inhibition than in those requiring response execution.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, like older children and adults (Kolodny et al, 2020;Mehnert et al, 2013;van Belle et al, 2014), 10-month-old infants activate the right parietal cortex when inhibition is required. This finding is consistent with recent evidence that the prefrontal and parietal cortex work in conjunction during early EF development (Fiske & Holmboe, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant association was found for ADHD core symptoms, our mediation analysis found a significant indirect effect of RNF219 ‐ AS1 rs3908461 on ADHD total symptom through executive inhibition as the mediator. Previous studies have found that children with ADHD exhibited a range of executive deficits, especially the inhibition function 49 . Family‐based behavioral genetics studies conducted in either ADHD 50 or general population 35 have suggested that inhibitory function—as an important executive function refers to the ability to control decision‐making, behaviors, and emotional impulse—is significantly heritable; and it may be considered a valid endophenotype of ADHD.…”
Section: Discussionmentioning
confidence: 99%